Bioactive glass-collagen/poly (glycolic acid) scaffold nanoparticles exhibit improved biological properties and enhance osteogenic lineage differentiation of mesenchymal stem cells - Toosi, Shirin; Naderi-Meshkin, Hojjat; Esmailzadeh, Zohreh; Behravan, Ghazal; Ramakrishna, Seeram; Behravan, Javad (Frontiers in Bioengineering and Biotechnology, 2022)
Today's using tissue engineering and suitable scaffolds have got attention to increase healing of non-union bone fractures. In this study, we aimed to prepare and characterize scaffolds with functional and mechanical properties suitable for bone regeneration. Porous scaffolds containing collagen-poly glycolic acid (PGA) blends and various quantities of bioactive glass (BG) 45S5 were fabricated. Scaffolds with different compositions (BG/collagen-PGA ratios (w/w): 0/100; 40/60; 70/30) were characterized for their morphological properties, bioactivity, and mechanical behavior. Then, biocompatibility and osteogenic differentiation potential of the scaffolds were analyzed by seeding mesenchymal stem cells (MSCs). Scaffolds made with collagen-PGA combined with the BG (45S5) were found to have interconnected pores (average pore diameter size 75 to 115 µm) depending on the percentage of the BG added. Simulated body fluid (SBF) soaking experiments indicated the stability of scaffolds in SBF regardless of their compositions, while the scaffolds retained their highly interconnected structure. The elastic moduli, cell viability, osteogenic differentiation of the BG/collagen-PGA 40/60 and 70/30 scaffolds were superior to the original BG/collagen-PGA (0/100). These results suggest that BG incorporation enhanced the physical stability of our collagen-PGA scaffold previously reported. This new scaffold composition provides a promising platform to be used as a non-toxic scaffold for bone regeneration and tissue engineering.